Unintentional Weight Loss and Its Role in Malnutrition Among Patients with Chronic Kidney Disease: A Narrative Review - Syafrida Nur Rochma; Kurnia Agustina Sitompul (Media Gizi Indonesia, 2026)
Unintentional weight loss is an important clinical indicator of malnutrition in patients with chronic kidney disease and frequently reflects the development of protein-energy wasting. This narrative review summarizes current evidence on its prognostic value, underlying mechanisms, and management strategies. A total of 17 studies published between January 2021 and March 2025 were identified through PubMed, Scopus, and Web of Science. Eligible studies included adults with chronic kidney disease in whom unintentional weight loss was examined in relation to nutritional status, protein-energy wasting, muscle mass, or mortality. The evidence consistently demonstrated that weight loss identified using the Subjective Global Assessment, Malnutrition-Inflammation Score, or Global Leadership Initiative on Malnutrition criteria was associated with increased mortality, functional decline, and poorer clinical outcomes. Contributing mechanisms include chronic inflammation, metabolic and hormonal alterations, nutrient losses during dialysis, and inadequate dietary intake resulting from gastrointestinal or sensory symptoms. Early recognition depends on regular weight monitoring supported by body composition and functional assessments. Management focuses on individualized nutritional therapy, rehabilitation, correction of metabolic acidosis, and symptom control. Overall, unintentional weight loss represents a practical, inexpensive, and reliable prognostic marker in chronic kidney disease. Routine screening and prompt intervention may improve clinical outcomes and quality of life.